HASIL BELAJAR KOGNITIF SISWA MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF TIPE WHO WANTS TO BE A MILIONER DIKELAS X SMA PGRI PEKANBARU PADA MATERI HUKUM NEWTON - Dwi Nyoman Kartika; Muhammad Nor; Zulhelmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak : The purpose of this research is to describe students’ cognitive learning result by using application of cooperative learning who wants to be a milioner in the tenth grade senior high school PGRI Pekanbaru on the lesson newton law with using design One Shut Case Study. Research done in high school PGRI 2 street of wisma number 7 Research begins december 2016 until may 2017, which total number were 21 students that is 11 male students and 10 female students using application of cooperative learning who wants to be a milioner The data on this research is in form of students’ scores taught by using application of cooperative learning who wants to be a milioner which is done at the end of the learning process by implementing and it is analyzed on descriptive. Based on the results of data analysis obtained the average absorbption 79,04% with good and effective category. Based on the result of the analysis, can be concluded application of cooperative learning who wants to be a milioner effective used to achieve students cognitive learning of senior high school PGRI Pekanbaru on the lesson newton law.Key Words: cooperative learning who wants to be a milioner, learning result